Faktor-Faktor yang Berhubungan dengan Kejadian Stunting pada Balita Usia 6-59 Bulan di Wilayah Kerja Puskesmas Benu-Benua Kota Kendari Tahun 2024 - Sarni S; Wa Ode Salma; Fithria Fithria (Jurnal Medika Nusantara, 2024)
Toddler Stunting is included in chronic nutritional problems caused by various factors such as socioeconomic conditions, maternal nutrition during pregnancy, lack of nutritional intake in infants and pain in infants, this study aims to find out the factors related to the incidence of stunting in toddlers aged 6-59 months in the BLUD UPTD Benu-Benua Health Center in Kendari City in 2024, This study uses a case control method with purposive sampling techniques. The results of the study were that family income was a risk factor for stunting with p values (0.015) and OR (2.153), parenting style was a factor for stunting with p values (0.004) and OR (3.125) and infectious diseases were not risk factors for stunting with p values (1,000) and OR (1,071)